1985
DOI: 10.1210/jcem-60-1-5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oxytocin-Like and Vasotocin-Like Peptide in Human Plasma after Administration of Estrogen*

Abstract: Using three antisera to oxytocin (OT Pitt Ab-1, OT Pitt Ab-2, and TOR OT Ab), we found comparable levels of OT in response to infant suckling and during infusion of synthetic OT, and identical standard curves with biological and synthetic standards of OT. Pitt Ab-1, but not Pitt Ab-2 or TOR OT Ab, measured increased OT in response to estrogen. Using an arginine vasotocin RIA (TOR AVT Ab), we found an increase in AVT immunoreactivity after estrogen treatment. Mean basal OT levels measured with OT Pitt Ab-2 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 13 publications
2
46
1
Order By: Relevance
“…Oxytocin was first extracted from plasma and then assayed using a specific oxytocin antibody (Pittsburgh Antibody 2) by Dr. Janet Amico of the University of Pittsburgh following previously published techniques (Amico et al, 1985;Amico, Johnston, & Vagnucci, 1994). The standard curve was linear between 0.5 and 10 pg/tube, and any sample less than 0.5 pg was designated as zero.…”
Section: Cardiovascular Urine and Blood Samplingmentioning
confidence: 99%
“…Oxytocin was first extracted from plasma and then assayed using a specific oxytocin antibody (Pittsburgh Antibody 2) by Dr. Janet Amico of the University of Pittsburgh following previously published techniques (Amico et al, 1985;Amico, Johnston, & Vagnucci, 1994). The standard curve was linear between 0.5 and 10 pg/tube, and any sample less than 0.5 pg was designated as zero.…”
Section: Cardiovascular Urine and Blood Samplingmentioning
confidence: 99%
“…Furthermore, this oxytocin-like peptide is detected only with Pittsburgh oxytocin an tibody 1, which was not used in the present study. Pittsburgh oxytocin antibody 2, which was used in the present study and in our prior studies of oxytocin in CSF, is specific for oxytocin as validated by HPLC and bioassay [23,24,41]. Therefore, the oxytocin immunoreactivity measured in CSF in the present study is likely authentic oxytocin.…”
Section: Discussionmentioning
confidence: 75%
“…We previously found that the oxytocin immunoreactivity in extracts of monkey and human CSF as well as monkey spinal cord eluted from an HPLC column in the position of synthetic oxytocin [5,40]. Although we had previously also found that humans and monkeys administered estrogen released an oxyto cin-like peptide into plasma [23], this oxytocin-like peptide was not found in CSF of Ei-treated primates. Furthermore, this oxytocin-like peptide is detected only with Pittsburgh oxytocin an tibody 1, which was not used in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…This assay has been described previously (Amico et al 1981(Amico et al , 1985. Briefly, a starting volume of 300-400 ml plasma was extracted using the acetone-ether method.…”
Section: Assaysmentioning
confidence: 99%